Leading Where Resources Are Limited: Lived Experiences and Adaptive Practices of Public Elementary School Principals in Rural Communities - RONALD BASUBAS (International Journal of Education, Literacies and Curriculum Studies, 2026)
School leadership in rural communities is shaped by conditions that extend beyond conventional administrative and instructional responsibilities. Public elementary school principals may encounter limited financial and instructional resources, infrastructure constraints, staffing concerns, competing administrative demands, and challenges in mobilizing community support while remaining responsible for sustaining teaching and learning. This qualitative phenomenological study explores the lived experiences and adaptive leadership practices of public elementary school principals working in resource-constrained rural communities. Specifically, it examines the challenges principals encounter, the strategies they employ to address resource limitations, the role of stakeholder collaboration in sustaining school operations, and the meanings they construct from their leadership experiences. Participants will be purposively selected public elementary school principals with direct experience leading rural schools. Data will be generated through in-depth semi-structured interviews and analyzed through phenomenologically informed thematic analysis. The study is anchored in Adaptive Leadership Theory and contextualized within the Philippine Professional Standards for School Heads. Recent Philippine research indicates that rural school leaders respond to resource scarcity through flexibility, community engagement, collaborative decision-making, resource mobilization, and context-sensitive problem-solving. The study is expected to contribute to the growing literature on context-responsive educational leadership by foregrounding principals' voices and examining how leadership is enacted when formal resources are insufficient. Findings may inform leadership development, resource-allocation policies, school-community partnerships, and institutional support for principals serving rural public schools.